Design of Automatic Irrigation System For Post-Mining Land Reclamation - Sihombing, Ruspita; Azizah, Amiril; Arifin, Zainal; Sari, Wahyuni Eka; Oscar, Agus Wiramsya; Putra, Pandhu Rochman Suosa (JOIV : International Journal on Informatics Visualization, 2025)
post-mining land reclamation poses a challenge in restoring degraded land's ecological function and productivity, requiring optimal rehabilitation to make it productive and environmentally friendly. A key challenge in reclamation is the availability of efficient water sources to support the revegetation process. Conventional irrigation systems are inefficient and require intensive monitoring. Therefore, an innovative solution in the form of an automatic irrigation system is needed to optimize water use and support sustainable plant growth. This study aims to design and develop a technology-based automatic irrigation system that combines soil moisture sensors, water pumps, sprinklers, solar panels, solenoid valves, and microcontrollers to regulate irrigation efficiently and on time. The methodology includes hardware and software design, integration of soil moisture sensors, a microcontroller as the control unit, and system field testing. The system is designed to activate irrigation based on real-time soil moisture levels automatically, ensuring water is only applied when needed. The system is expected to reduce excess water use and improve irrigation effectiveness across large and diverse areas. Results show that this automatic irrigation system can reduce water consumption by 34.2% compared to conventional methods. In addition, farmers can remotely manage irrigation via the Internet or mobile apps, reducing irrigation time by 75 minutes. This system holds the potential to be an innovative and sustainable solution for post-mining land reclamation, ushering in a new era of efficient and sustainable agriculture.